Pengaruh Metode Numbered Heads Together (NHT) Terhadap Hasil Belajar Pada Mata Pelajaran Al-Qur’an Hadits Siswa Kelas V Madrasah Ibtidaiyah Muhammadiyah 14 Sumurgayam Paciran Lamongan - Hilma, Intan Aulia; Santoso, Subhan Adi (STIT Muhammadiyah Paciran, 2021)
is there a difference in student learning outcomes before using the Numbered Heads Together (NHT) method with student learning outcomes after using the Numbered Heads Together (NHT) method. the effect of the Numbered Heads Together (NHT) method on student learning outcomes in the subjects of Al-Qur'an Hadith for fifth grade students at MI 14 Muhammadiyah Sumurgayam Paciran From the results of data analysis, it was found that student learning outcomes had increased. In the pretest, the average score of students was 47.27 with classical learning completeness of 18.18%. In the posttest questions the average value of students is 76.81 with classical learning mastery reaching 72.72%. Thus, it can be said that learning using the Numbered Heads Together (NHT) method can improve student learning outcomes in the subjects of Al-Qur'an Hadith for fifth grade students at MI 14 Muhammadiyah Sumurgayam.